2017 MEDAM Assessment Report on Asylum and Migration Policies in Europe. Sharing responsibility for refugees and expanding legal immigration - Esther Ademmer; Mehtap Akgüç; Mikkel Barslund; Anna Di Bartolomeo; David Benček; Dominik Groll; Rezart Hoxhaj; Mauro Lanati; Nadzeya Laurentsyeva; Matthias Lücke; Lars Ludolph; Afaf Rahim; et al. (Kiel Institute for the World Economy (IfW), 2017)
How can the responsibility for refugees be distributed more fairly – globally and within the EU? And how can we curb irregular migration while expanding legal immigration to the benefit of all concerned? The large number of refugees and other migrants who have come to Europe over the last two years has caused the EU member states that received most of the asylum seekers, to reach their capacity limits. With a view to new arrivals and their long-term integration, it is now necessary to develop new and, above all, common strategies to address the migration flows to Europe. The '2017 MEDAM Assessment Report' focuses on two core Messages: - Distribute the responsibility for refugees more equitably. - Extending legal immigration from non-EU Member States into EU member states. – – Wie kann die Verantwortung für Flüchtlinge weltweit und in Europa gerechter verteilt werden? Und wie können wir irreguläre Einwanderung eindämmen und gleichzeitig die legale Einwanderung zum Nutzen aller Beteiligten fördern? Durch die große Zahl an Flüchtlingen und andere Migranten, die Europa in den vergangenen beiden Jahren erreicht haben, wurden insbesondere jene EU-Staaten, die die meisten Asylsuchenden aufgenommen haben, an ihre Kapazitätsgrenzen gebracht. Mit Blick auf weitere Neuankömmlinge und deren langfristige Integration ist es nun notwendig, neue und vor allem gemeinsame Strategien zur Bewältigung der Flüchtlingsströme nach Europa zu erarbeiten. Im Fokus des "2017 MEDAM Assessment Report on Asylum and Migration Policies in Europe" stehen zwei Handlungsempfehlungen: - Die Verantwortung für Flüchtlinge weltweit und in Europa gerechter verteilen. - Die legale Einwanderung von außerhalb der EU in EU-Mitgliedstaaten erleichtern.
Keywords: 320